The "Xokleng Case": historical events and territorial environmental conflicts in the Ibirama-Laklãnõ Indigenous Land (Tempo e Argumento, 2023)
The Ibirama-LaKlãnõ Indigenous Land is inhabited by three ethnic groups: Xokleng, Kaingang, and Guarani Mbyá. Historically this TI is marked by several territorial environmental conflicts and a confusing and controversial territorialization process. The present article seeks to systematize the main historical facts that defined the limits of the demarcation of the IT and to discuss the categories of conflicts related to the history of this land. For this purpose a documental survey was done, as well as the collection of testimonies in the field, with "elders" and leaders, a map with the graphic representation of the areas in dispute and conflicts, and the systematization of the information. The result is that State institutions, politicians, and some sectors of private enterprise have been characterized as the main social antagonists, configuring conflicts as territorial domination, contingency and restriction of free access, assassinations, violence and torture, guardianship, environmental impacts by large projects, territorial expropriation, territorial invasion, timber theft, collusion and use of political power, and flooding of the territory.
Keywords: indigenous; territoria rights; desterritorialization; Santa Catarina